PD-1 blockade in neoadjuvant setting of DNA mismatch repair-deficient/microsatellite instability-high colorectal cancer. (1st January 2020) - Liu, Ding-Xin; Li, Dan-Dan; He, Wan; Ke, Chuan-Feng; Jiang, Wu; Tang, Jing-Hua; Kong, Ling-Heng; Li, Yuan; Sui, Qiao-Qi; Xiao, Bin-Yi; Li, Wei-Rong; Hong, Zhi-Gang; et al.
ABSTRACT: Background : Although PD-1 blockade has significantly improved the survival of metastatic colorectal cancer with DNA Mismatch Repair-Deficient/Microsatellite Instability-High (MSI-H), the data on neoadjuvant setting is limited. Methods : In this retrospective study, we enrolled eight patients with advanced MSI-H colorectal cancer from three hospitals. Four patients are locally advanced and four are metastatic. All the patients received at least two doses of PD-1 antibody with or without chemotherapy as neoadjuvant therapy. The aim of the present study was to evaluate the short-term efficacy and toxicities of this strategy. Results : All the enrolled eight patients had a major response in imaging and/or pathological evaluation. Five of the seven resected patients were evaluated as pathological complete response. One patient without surgery has a clinical complete response (cCR) tumor response. Conclusions : Neoadjuvant PD-1 blockade induced tumor regression with a major clinical and pathological response in advanced dMMR/MSI-H colorectal cancer. Further studies are required to evaluate the long-term effect of this strategy.